Resolution of occult anastomotic stricture with anal dilator: challenges with the conventional diagnostic criteria in low anterior rectal resection patient—a case report - Cao, Gaoyang; Zhang, Xinjie; Wu, Songtao; Zhou, Wei (Frontiers in Oncology, 2024)
Background: Anastomotic stricture (AS) is a common complication following rectal cancer surgery with anastomosis, but its diagnosis and management pose significant challenges due to the lack of standardized diagnostic criteria. We present a case highlighting the complexities encountered in diagnosing and managing occult AS postrectal cancer surgery. Case Presentation: A 51-year-old male, post-robot-assisted laparoscopic low anterior resection for rectal adenocarcinoma, presented with symptoms suggestive of AS. Despite conventional evaluations, including colonoscopy, digital rectal examination and radiography, AS was not identified. Following prolonged and ineffective treatment for suspected conditions such as Low Anterior Resection Syndrome (LARS), the patient underwent anal dilatation, resulting in significant symptom improvement. Conclusion: This case underscores the challenges associated with diagnosing and managing occult AS following rectal cancer surgery. The absence of standardized diagnostic criteria and reliance on conventional modalities may lead to underdiagnosis and inadequate treatment. A comprehensive diagnostic approach considering intestinal diameter, elasticity, and symptoms related to difficult defecation may enhance diagnostic accuracy. Further research is needed to refine diagnostic and therapeutic strategies for occult AS.